2018
DOI: 10.3390/w10111685
|View full text |Cite
|
Sign up to set email alerts
|

Review of Constructed Wetlands for Acid Mine Drainage Treatment

Abstract: The mining industry is the major producer of acid mine drainage (AMD). The problem of AMD concerns at active and abandoned mine sites. Acid mine drainage needs to be treated since it can contaminate surface water. Constructed wetlands (CW), a passive treatment technology, combines naturally-occurring biogeochemical, geochemical, and physical processes. This technology can be used for the long-term remediation of AMD. The challenge is to overcome some factors, for instance, chemical characteristics of AMD such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 110 publications
(184 reference statements)
1
49
0
1
Order By: Relevance
“…Successfully used floating aquatic plants in the treatment of mine effluents include Salvinia natans, Pistia stratiotes, Eichornia crassipes [239,288]. Submerged aquatic macrophytes like Ceratophylum demersum, Cabomba piauhyensis, Egeria densa, Myriophylum spicatum and Hydrilla verticillata are recommended to be used for the phytoremediation of mine effluents as they have shown outstanding ability to accumulate HMs in their whole body biomass [289,290].…”
Section: Phytoremediation Of Mining Effluentsmentioning
confidence: 99%
“…Successfully used floating aquatic plants in the treatment of mine effluents include Salvinia natans, Pistia stratiotes, Eichornia crassipes [239,288]. Submerged aquatic macrophytes like Ceratophylum demersum, Cabomba piauhyensis, Egeria densa, Myriophylum spicatum and Hydrilla verticillata are recommended to be used for the phytoremediation of mine effluents as they have shown outstanding ability to accumulate HMs in their whole body biomass [289,290].…”
Section: Phytoremediation Of Mining Effluentsmentioning
confidence: 99%
“…For example, it can be used profitably in subsequent effluent treatment experiments to meet the initial nutrients requirement for the establishment of plants in CWs. Pat-Espadas et al [56] suggested the use of residual waste as construction material to avoid undesirable environmental and health effects.…”
Section: Discussionmentioning
confidence: 99%
“…Constructed wetlands have been widely used in the treatment of primary or secondary domestic sewage effluents, and others have been used to treat domestic wastewater and have also been modeled to handle high organic loads associated with agriculture or domestic wastewater [5]. A large number of constructed wetlands have also been built to treat drainage from active and abandoned coal mines [20]. The constructed wetland technology has recently been used in the control and management of stormwater flows, and its application in reducing the impacts by stormwater floods within urban areas is expanding globally [21].…”
Section: Constructed Wetlandsmentioning
confidence: 99%